Amyloid β-Related Central Nervous System Angiitis Presenting With an Isolated Seizure. (April 2014) - Ishii, Makoto; Lavi, Ehud; Kamel, Hooman; Gupta, Ajay; Iadecola, Costantino; Navi, Babak B.
Amyloid beta-related angiitis (ABRA) of the central nervous system (CNS) is a very rare inflammatory disorder that causes destruction of CNS arteries and subsequent neuronal injury. Most patients with ABRA are old and present with cognitive dysfunction and stroke; however, some patients may present atypically. In this article, we report a 44-year-old man who presented with a first-time seizure but was otherwise neurologically intact and denied any headache. Brain MRI showed right hemispheric and bilateral medial frontal lobe hyperintensities and microhemorrhages that were most suspicious for a mass lesion. An extensive diagnostic evaluation including CSF analysis and catheter angiography was unremarkable. A brain biopsy with specific stains for amyloid surprisingly demonstrated ABRA and led to immunosuppressive treatment. The patient has remained neurologically intact and seizure-free 1 year after presentation. This case demonstrates that ABRA can occur in young patients without headache or neurologic deficits, and should be considered in patients with new-onset seizures and mass lesions. It also reinforces the need to consider a brain biopsy in patients with idiopathic brain lesions and negative non-invasive testing, as it is virtually impossible to confirm the diagnosis of ABRA otherwise.